2020
DOI: 10.1155/2020/1948602
|View full text |Cite
|
Sign up to set email alerts
|

Honeybush Extracts (Cyclopia spp.) Rescue Mitochondrial Functions and Bioenergetics against Oxidative Injury

Abstract: Mitochondrial dysfunction plays a major role not only in the pathogenesis of many oxidative stress or age-related diseases such as neurodegenerative as well as mental disorders but also in normal aging. There is evidence that oxidative stress and mitochondrial dysfunction are the most upstream and common events in the pathomechanisms of neurodegeneration. Cyclopia species are endemic South African plants and some have a long tradition of use as herbal tea, known as honeybush tea. Extracts of the tea are gainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Mitochondria are the main generators of ROS and are directly affected by their overproduction. At the same time, neurons are highly dependent on mitochondria for their function and survival as they demand high amounts of energy, while they are more vulnerable to oxidative stress [44][45][46]. In our study, Dexa significantly increased the levels of mitochondrial ROS, cytosolic ROS, and mitochondrial superoxide anion in both cell lines.…”
Section: Discussionsupporting
confidence: 56%
“…Mitochondria are the main generators of ROS and are directly affected by their overproduction. At the same time, neurons are highly dependent on mitochondria for their function and survival as they demand high amounts of energy, while they are more vulnerable to oxidative stress [44][45][46]. In our study, Dexa significantly increased the levels of mitochondrial ROS, cytosolic ROS, and mitochondrial superoxide anion in both cell lines.…”
Section: Discussionsupporting
confidence: 56%
“…Commercial cultivation and factory-based production have increased the access and value of honeybush tea. Extracts of the tea are gaining more scientific attention due to their phenolic composition (Agapouda et al, 2020). Athrixia phylicoides DC.…”
Section: Prioritisation Of Functional Medicinal Plantsmentioning
confidence: 99%
“… 22 Mitochondria are the powerhouses of eukaryotic cells, which generate ATP via the mitochondrial electron transport chain (ETC) through oxidative phosphorylation (OXPHOS). 23 , 24 In addition to ATP production, mitochondria also produce ROS as a byproduct of OXPHOS. 25 It has been reported that the occurrence of ischemic stroke is often associated with energy metabolism disorder, including mitochondrial functional impairment and imbalance of ion homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral ischemia induces mitochondrial dysfunction and adenosine triphosphate (ATP) depletion . Mitochondria are the powerhouses of eukaryotic cells, which generate ATP via the mitochondrial electron transport chain (ETC) through oxidative phosphorylation (OXPHOS). , In addition to ATP production, mitochondria also produce ROS as a byproduct of OXPHOS . It has been reported that the occurrence of ischemic stroke is often associated with energy metabolism disorder, including mitochondrial functional impairment and imbalance of ion homeostasis. , Na + -K + -ATPase and Ca 2+ -Mg 2+ -ATPase are important regulators of Ca 2+ homeostasis, which are key indicators of energy metabolism. For this reason, mitochondria is thought to be an important target of organelles in cerebral ischemia, and the cause of its injury is the key link to cerebral ischemia injury .…”
Section: Introductionmentioning
confidence: 99%